Regulation of corn starch on the properties of tremella polysaccharide-egg white protein-orange juice composite gel and its application in 3D printing - Lili Liu; Beibei Shao; Wanlin Yang; Weiwei Cheng; Yue Ding; Feng Xiao (Food Chemistry: X)
The purpose of this paper was to explore the regulation of corn starch (CS) on tremella fuciformis polysaccharide-egg white protein-orange juice (TFP-EWP-OJ) composite gel to develop a new 3D printing material. The results showed that the cylinder of TFP-EWP-OJ composite gel with 0.12 g/mL CS added had the best 3D printing structure and highest printing accuracy. This was an indication that materials with suitable viscosity, hardness, and flowability were more suitable for 3D printing. The nozzle diameter and printing speed were selected to be 1.20 mm and 35 mm/s, respectively. The TFP-EWP-OJ composite gel had greater apparent viscosity and hardness as well as weaker fluidity and a denser network structure with increasing CS concentration. This suggested that the 3D printing performance of TFP-EWP-OJ composite gel can be improved by the incorporation of CS. Furthermore, fourier transform infrared spectroscopy (FT-IR) indicated that no new covalent bonds were formed between CS and the TFP-EWP-OJ composite gel.